Analysis of nucleon electromagnetic form factors from light-front holographic QCD: The spacelike region - Sufian, Raza Sabbir; Dosch, Hans Günter (Physical review, 2017)
We present a comprehensive analysis of the spacelike nucleon electromagnetic form factors and their flavor decomposition within the framework of light-front (LF) holographic QCD (LFHQCD) We show that the inclusion of the higher Fock components |qqqq¯q⟩ has a significant effect on the spin-flip elastic Pauli form factor and almost zero effect on the spin-conserving Dirac form factor. We present light-front holographic QCD results for the proton and neutron form factors at any momentum transfer range, including asymptotic predictions, and show that our results agree with the available experimental data with high accuracy. In order to correctly describe the Pauli form factor we need an admixture of a five quark state of about 30% in the proton and about 40% in the neutron. We also extract the nucleon charge and magnetic radii and perform a flavor decomposition of the nucleon electromagnetic form factors. The free parameters needed to describe the experimental nucleon form factors are very few: two parameters for the probabilities of higher Fock states for the spin-flip form factor and a phenomenological parameter r, required to account for possible SU(6) spin-flavor symmetry breaking effects in the neutron, whereas the Pauli form factors are normalized to the experimental values of the anomalous magnetic moments. The covariant spin structure for the Dirac and Pauli nucleon form factors prescribed by AdS5 semiclassical gravity incorporates the correct twist scaling behavior from hard scattering and also leads to vector dominance at low energy.